Characterization of (1)H NMR Signal in Human Cortical Bone for Magnetic Resonance Imaging - Horch, R. Adam (2010)
Recent advancements in magnetic resonance imaging (MRI) have enabled clinical imaging of human cortical bone (HCB), providing a potentially powerful new means for assessing bone health with molecular-scale sensitivities unavailable to conventional X-ray-based diagnostics. In HCB, MRI is sensitive to populations of protons ((1)H) partitioned among water and protein sources, which may be differentiated according to intrinsic nuclear magnetic resonance (NMR) properties such as chemical shift and transverse and longitudinal relaxation rates. Herein, these NMR properties were assessed in HCB donors from a broad age range, and four distinct (1)H populations were consistently identified and attributed to five microanatomical sources. These findings show that modern HCB MRI contrast will be dominated by collagen-bound water, which can also be exploited to study HCB collagen via magnetization transfer.